Characteristics of fired clay bricks with waste marble powder addition as building materials. (1st May 2015) - Sutcu, Mucahit; Alptekin, Hande; Erdogmus, Ertugrul; Er, Yusuf; Gencel, Osman
Highlights: Fired clay bricks with marble waste were studied. Addition of waste marble powder increases thermal performance of brick. Bricks have enough strength required by standard. Increasing of firing temperature affects mechanical and physical properties of bricks. Abstract: Fired clay bricks lightened by adding up to 35 wt.% waste marble powder have been produced by semi-dry pressing process. Chemical composition, phase identification, thermal behavior and microstructure of the raw materials were analyzed by XRF, XRD, TGA and SEM, respectively. The brick mixtures containing waste marble powder at different proportions were formed, dried and then fired at 950 and 1050 °C for 2 h. Properties such as drying and firing shrinkages, loss on ignition, bulk density, porosity, water absorption, compressive strength, thermal conductivity, microstructure and phase content of the fired brick samples were determined. It was found that the use of waste marble powder addition reduced the bulk density of the samples. It was observed that their porosity ratios up to about 40% improved with increasing of waste marble powder addition up to 30 wt.% for all samples, whereas their compressive strengths decreased until 8.2 MPa. However, their strengths were enough according to the values required by the standards. Thermal conductivity of the samples decreased from 0.97 to 0.40 W/mK. Increasing of the firing temperature also affected their mechanical and physical properties. This study showed that the waste marble powders could be used as a pore maker and contributing to the formation of crystalline phases in brick production at certain ratios.